1799 Ky. Acts 7, An Act to Amend an Act Entitled “An Act Concerning the Militia,” p. 421-22, §§ 1-3. - (:unkn) unknown (General Publisher, 1799)
[T]he brigadier generals shall attend each regimental muster within their brigades to view the same; it shall be the duty of the brigade major, attended by the commandant of the regimnt, to inspect the same at every muster. § 2. All fines arising within the bounds of any regiment, on account of delinquencies of officers, privates, or otherwise, shall be appropriated to the use of such regiment only. § 3. . . . [E]ach non-commissioned officer shall have ten days notice of each muster; and each non-commissioned officer and private, appearing on parade without a gun after being duly notified, shall be fined any sum not exceeding fifty cents, at the discretion of a court martial.
--
Keywords: ARMED FORCES